2017
DOI: 10.1186/s10194-017-0741-2
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide and pain: a systematic review

Abstract: BackgroundCalcitonin gene-related peptide (CGRP) is widely distributed in nociceptive pathways in human peripheral and central nervous system and its receptors are also expressed in pain pathways. CGRP is involved in migraine pathophysiology but its role in non-headache pain has not been clarified.MethodsWe performed a systematic literature search on PubMed, Embase and ClinicalTrials.gov for articles on CGRP and non-headache pain covering human studies including experimental studies and randomized clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(154 citation statements)
references
References 116 publications
(161 reference statements)
6
146
1
1
Order By: Relevance
“…The release of calcitonin gene–related peptide (CGRP) by sensory neurons is implicated in the pathophysiology of numerous pain disorders (18, 19). The classic nociceptive mediator prostaglandin E 2 (PGE 2 ) does not significantly alter CGRP release at 1 μM concentrations at neutral pH (20, 21); however, PGE 2 augments CGRP release evoked by low pH (which mimics an inflammatory state) or capsaicin (which activates ion channels involved in nociception) (20, 21), indicating DRG sensitization.…”
Section: Resultsmentioning
confidence: 99%
“…The release of calcitonin gene–related peptide (CGRP) by sensory neurons is implicated in the pathophysiology of numerous pain disorders (18, 19). The classic nociceptive mediator prostaglandin E 2 (PGE 2 ) does not significantly alter CGRP release at 1 μM concentrations at neutral pH (20, 21); however, PGE 2 augments CGRP release evoked by low pH (which mimics an inflammatory state) or capsaicin (which activates ion channels involved in nociception) (20, 21), indicating DRG sensitization.…”
Section: Resultsmentioning
confidence: 99%
“…Both approaches have shown efficacy in clinical trials, but the receptor antagonists have been discontinued owing to liver toxicity . Intriguingly, CGRP levels in plasma, synovial, and cerebrospinal fluid and tissue biopsies are elevated and correlated to pain in individuals with degenerative disc disease and osteoarthritis . Thus, it has been proposed that CGRP may be a critical factor also in non‐migraine pain, but this remains to be defined.…”
Section: What We Need To Knowmentioning
confidence: 99%
“…Additionally, our results recovered relationship between migraine and joint pains, this could be interpreted in the light of the CGRP induced synovitis, where it was found that CGRP contributes to transition from normal to persistent synovitis, and the progression from nociception to sensitization [39]. Also, CGRP may play a role in pain transmission in somatic pain conditions such as joint and muscular chronic pain [40].…”
Section: Discussionmentioning
confidence: 94%